2022
DOI: 10.1098/rspb.2022.1102
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity cradles and museums segregating within hotspots of endemism

Abstract: The immense concentrations of vertebrate species in tropical mountains remain a prominent but unexplained pattern in biogeography. A long-standing hypothesis suggests that montane biodiversity hotspots result from endemic species aggregating within ecologically stable localities. Here, the persistence of ancient lineages coincides with frequent speciation events, making such areas both ‘cradles’ (where new species arise) and ‘museums’ (where old species survive). Although this hypothesis refers to processes op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 65 publications
0
20
1
Order By: Relevance
“…The presence of genera exclusively associated with a single belt is mainly related to the occurrence of mountain systems, such as Celisaltica in the Ruwenzori Massif (Uganda), Perichilona in the Iringa region (Tanzania), Upembaltica in the Katanga region (Democratic Republic of Congo), and Drakensbergianella in the Drakensberg Mountains (Democratic Republic of South Africa). This is not surprising, considering the acknowledged role of tropical mountains as "cradles" and/or "museums" of biodiversity [10,11,[61][62][63]. Indeed, although other mountains, such as Mount Kenya, Mount Aberdare, and Mount Kilimanjaro, lack endemic flea beetle genera, they nonetheless host several endemicities at the species level.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of genera exclusively associated with a single belt is mainly related to the occurrence of mountain systems, such as Celisaltica in the Ruwenzori Massif (Uganda), Perichilona in the Iringa region (Tanzania), Upembaltica in the Katanga region (Democratic Republic of Congo), and Drakensbergianella in the Drakensberg Mountains (Democratic Republic of South Africa). This is not surprising, considering the acknowledged role of tropical mountains as "cradles" and/or "museums" of biodiversity [10,11,[61][62][63]. Indeed, although other mountains, such as Mount Kenya, Mount Aberdare, and Mount Kilimanjaro, lack endemic flea beetle genera, they nonetheless host several endemicities at the species level.…”
Section: Discussionmentioning
confidence: 99%
“…It was generally believed that species turnover among communities was jointly driven by ecological processes such as diffusion limitation and environmental ltration, while species richness differences among communities were mainly driven by habitat ltration on regional environmental gradients (Jamoneau et al 2018). Many studies believed that species turnover components are the main contributions of beta diversity differences in forest (Wang et al 2018;Sonne et al 2022). Thus, beta diversity differences in forest are mainly caused by diffusion limitation and environmental ltration.…”
Section: Beta Diversity and Its Decomposition Of Karst Forest Along L...mentioning
confidence: 99%
“…However, a significant distinction between the study on neotropical birds and the current paper lies in the fact that the former used branch length and its evolutionary relationships within the tree of life analysed under phylogenetic null models. Consequently, due to the methodological differences, an additional layer of evolutionary information has been introduced to further support the theory, as demonstrated in recent studies [7]. royalsocietypublishing.org/journal/rsos R. Soc.…”
Section: Cradles and Museums Of Biodiversitymentioning
confidence: 99%
“…The northern Andes have been considered an area capable of harbouring both cradles and museums of biodiversity [1,5]. For example, in the case of tropical hummingbird species, research has revealed that the Andean mountain ranges of Colombia contain localized areas with endemic species of both recent (young) and ancient (old) origin [7]. In fact, the Sierra Nevada de Santa Marta, which is an isolated massif, represents the clearest example of a cradle for young endemic species in Colombia, while the western mountain range displays more characteristics of a museum for endemic hummingbird species [7].…”
Section: Introductionmentioning
confidence: 99%